Measuring the Impact of Urban Air Pollution: Hedonic Price Analysis and Health Production Function - Endah Saptutyningsih; Ahmad Ma’ruf (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2015)
This study aims to value air quality from the urban housing market in Yogyakarta City. It is also provides estimation of marginal willingness to pay for the air quality improvement and estimation of the consumer surplus due to reduce of air quality. The methodological framework for estimation is based on a hedonic price model. The result of hedonic price method concludes that by adopting a two-stage estimation procedure to estimate the relationship between air quality and property value, on the average, an increase in the level of O3 by one percent will increases the property price by 0.063 percent. By using a health production function and demand function mitigation can be seen that the medical history of the individual has effect on the number of working days lost. Meanwhile, O3 pollution has positive effect on the amount of medical expenses for mitigation. Decreasing in O3 pollution causes a decrease in the level of medical expenses to mitigate. Therefore, it is important to reduce the negative impacts of air pollution.